ANALISIS PENGARUH JENIS BAHAN BAKAR B0, B30, B35, DAN B40 TERHADAP EFISIENSI THERMAL PLTD BIAK - Syi’ar Mulya Ahmad Pratiknyo; Christiono (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
Diesel Power Plants (PLTD) play an important role in supplying electrical energy, particularly in island regions and remote areas such as Biak. To support the national energy transition, the government has implemented a mandatory biodiesel policy that has progressively increased from B30 and B35 to B40 in order to reduce dependence on fossil fuels. This study aims to analyze the thermal efficiency of PLTD Biak under B0, B30, B35, and B40 fuel types, as well as their effects on Specific Fuel Consumption (SFC) and heat rate. The research employed a quantitative descriptive approach using actual operational data, including fuel consumption, generator output power, and fuel heating values. The results show that increasing biodiesel content causes SFC to rise from 0.251 liter/kWh for B0 to 0.271 liter/kWh for B40, reduces thermal efficiency from 39.8% to 37.1%, and increases heat rate from 9,045 kJ/kWh to 9,704 kJ/kWh. It can be concluded that B30 provides the best balance between supporting the mandatory biodiesel policy and maintaining operational performance, while B35 and B40 require optimization of operating parameters to preserve efficiency.